The Influence of Taxpayer Awareness, Tax Sanctions, Tax Service Quality, and Tax Knowledge on The Individual Taxpayer Compliance - Santoso, Steven Miracle; Pontoh, Grace T.; Said, Darwis (Journal of Applied Business, Taxation and Economics Research, 2024)
Taxpayers are increasing from year to year, but this is not balanced with decreasing taxpayer compliance. This study aims to examine and analyze the level of individual taxpayer compliance with construct determined by taxpayer awareness, tax sanctions, tax service quality, and tax knowledge. The data of study used primary data obtained from a questionnaire disseminated to respondents in the Gowa Regency of 79 respondents. The results of the study showed that taxpayer awareness has a significant influence on taxpayer compliance, tax sanction has a significant influence on taxpayer compliance, tax service quality has a significant influence on taxpayer compliance, and tax knowledge has a significant influence on taxpayer compliance. This indicates that taxpayer awareness, tax sanctions, tax service quality, and tax knowledge can increase individual taxpayer compliance